2014
DOI: 10.1007/s11274-014-1662-8
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation by spray drying of nitrogen-fixing bacteria associated with lupin nodules

Abstract: Plant growth promoting bacteria and nitrogen-fixing bacteria (NFB) used for crop inoculation have important biotechnological potential as a sustainable fertilization tool. However, the main limitation of this technology is the low inoculum survival rate under field conditions. Microencapsulation of bacterial cells in polymer matrices provides a controlled release and greater protection against environmental conditions. In this context, the aim of this study was to isolate and characterize putative NFB associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
2
26
0
3
Order By: Relevance
“…The results obtained by Schoebitz et al (2012) confirm this statement as these authors demonstrated that a large proportion of cells are destroyed during capsule dehydration. In fact, cell mortality during the drying of encapsulated cells has been recognized as a critical point of the encapsulation process by various authors (Bashan et al 2002;Campos et al 2014). The survival yield after drying did not exceed 1 % of the initial cell count for various Azospirillum and Pseudomonas species.…”
Section: Ionic Gelationmentioning
confidence: 99%
See 3 more Smart Citations
“…The results obtained by Schoebitz et al (2012) confirm this statement as these authors demonstrated that a large proportion of cells are destroyed during capsule dehydration. In fact, cell mortality during the drying of encapsulated cells has been recognized as a critical point of the encapsulation process by various authors (Bashan et al 2002;Campos et al 2014). The survival yield after drying did not exceed 1 % of the initial cell count for various Azospirillum and Pseudomonas species.…”
Section: Ionic Gelationmentioning
confidence: 99%
“…Other studies have confirmed these observations, also reporting that the lowest air temperature was associated with the highest survival rate for the microorganisms during the drying process (Gardiner et al 2000;Golowczyc et al 2010). In fact, Campos et al (2014) reached a bacterial survival of 91 % for Enterobacter sp. immobilized using sodium alginate and maltodextrin as wall materials (2:13 w/w), feed flow rate of 73 m 3 h À1 , inlet temperature of 100 C, and outlet temperature of 65 C. In contrast, Schoebitz et al (2013b) found lower cell survival after the encapsulation of microorganisms such as Serratia sp., using only maltodextrin as wall material, inlet temperature of 145 C, and outlet temperature of 90 C. In this sense, the type of strain, temperature of the drying process, and formulations of the polymer mixture used as vehicles are important parameters for the encapsulation of beneficial microorganism in order to obtain a successful microbial inoculant.…”
Section: Spray Dryingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ürünlerin içerisindeki suyun uzaklaflt›r›lmas›, depolama ve tafl›ma maliyetlerinin azalt›lmas› ve ürünlerin spesifik özelliklerinin korunmas› amac›yla g›da sanayinde yayg›n olarak kullan›lan bu yöntem, süttozu üretimi ile birlikte gelifltirilmifltir. Sprey kurutma yöntemi en yayg›n ve en ucuz teknik olmas›na ra¤men bu yöntemde kapsülleme amac›yla tercih edilecek olan materyal seçimi oldukça önemlidir (27)(28)(29). Uygulamada atomizer içerisinde hem çekirdek ad› verilen kaplanacak materyal hem de kaplama materyali bir arada bulunmaktad›r.…”
Section: Bakteri̇yofaj Enkapsülasyonu Potansi̇yel Uygulamalariunclassified